INTEGRASI NILAI SPIRITUAL DALAM ENTERPRISE RISK MANAGEMENT (ERM): SEBUAH TINJAUAN PUSTAKA (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to develop a conceptual framework for integrating spiritual values into Enterprise Risk Management (ERM) as an ethical foundation for organizational risk governance. Employing a qualitative approach through a systematic–narrative literature review, the study analyzes ten internationally and nationally indexed articles addressing spirituality, ethics, and risk management. The synthesis reveals four main themes: technical rationality and spiritual wisdom, transcendental ethics in risk-taking, corporate spirituality and risk culture, and an integrative ERM model grounded in spiritual values. The resulting conceptual model consists of three  pillar sindividual spiritual awareness, organizational ethics and culture, and corporate moral governance which collectively form a risk management system oriented toward balancing technical efficiency and moral responsibility. This study underscores the importance of spiritual values as a foundation for ethical and sustainable human-centered governance.